PERANCANGAN DAN PENGEMBANGAN SISTEM INFORMASI WEBSITE SEKOLAH (STUDI KASUS : SEKOLAH TK AL-FAJAR) - Pranata, Angga; Zulanggara, Rizky; waskito, Wasis; Haryono, Wasis (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Pamulang, 2023)
Schools are one of the educational institutions that are very useful for the intellectual life of the nation and state. In the world of education, a technology is needed that can convey information accurately and quickly. An information is one of the very important needs of society. This research examines the development of a school information system in AL-FAJAR Kindergarten that can integrate all existing processes in the school with related data. The integration is carried out to increase efficiency in terms of resources used by the school and to provide structured data storage media. This system was developed using a programming language as a database server and tools using activity diagrams, use cases and sequences. The development of the school information system uses the Schoolhost Management System content development methodology. This system is expected to assist and support the process of collecting, processing, and managing data or information, as well as the implementation of teaching and learning in schools.